The Effect of Price Discounts and Sales Promotions on the Increase of Medicine Sales Volume at PT MBF Surabaya - Suprihono, Suprihono; Zaman, Komarun; Pratama, Devangga Putra Adhitya (Dinasti International Journal of Management Science, 2025)
This study investigates the effect of price discounts and sales promotions on the sales volume of pharmaceutical products at PT. MBF Surabaya, a distributor operating in a competitive market environment. The research was motivated by fluctuating sales performance and the company’s reliance on discount schemes and promotional activities as key marketing strategies. The objective was to analyze the individual and combined influence of discounts and promotions on sales outcomes. A quantitative associative method was employed, using structured questionnaires distributed to 32 respondents consisting of marketing staff and customers, supported by internal sales data. Data were analyzed through multiple linear regression, validity and reliability testing, as well as classical assumption tests. The results revealed that both discounts and sales promotions significantly increase sales volume, with promotions contributing more strongly than discounts. Simultaneous testing showed that 72% of the variance in sales volume was explained by the two variables combined. The findings highlight the importance of integrating financial incentives with creative promotional strategies to sustain competitiveness.